AN ANALYSIS OF STUDENTS’ ERROR IN WRITING DESCRIPTIVE TEXT AT TENTH GRADE STUDENTS IN SMK N 2 PADANGPANJANG - Efri Yoni, Rini Hendrita Ridha Jusni Sondra (Inovasi Pendidikan, 2025)
Error analysis is a method for identifying faults in foreign language learning. This study used error analysis to examine writing errors in descriptive text made by tenth-grade students at SMK N 2 Padangpanjang. It used a qualitative descriptive method and descriptive writing tests as instruments. The sample consisted of 20 tenth-grade students from SMK N 2 Padangpanjang. The aim of this research is to analyze the errors and causes of the errors made by students in writing descriptive text.The results of the study showed that tenth-grade students at SMK N 2 Padangpanjang made 33 errors in their writing. These errors were classified into categories including addition, omission, formation, and ordering. The highest frequency of error was omission (39.39%), followed by formation errors (36.36%), addition errors (18.18%), and ordering errors (6.06%) which had the lowest frequency.